(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2021)
This study aims to find out and explain the things that are considered in cases of theft committed by children, in the same case and still there are differences in considerations, so there are disparities in decisions. The data of this study were obtained using an empirical juridical approach. Problem analysis is done by processing secondary data, as well as direct interviews with respondents. The results of the study explain that to determine the decision must go through several considerations. The cause of the disparity in the decisions of child theft cases, especially in decisions Number 15/pid.sus-anak/2018/PN.Sbr and Number 30/pid.sus-anak/2021/PN.Sbr is caused by external factors, namely the Constitution of the Republic of Indonesia. Indonesia in 1945 where judges were given the freedom to administer justice, including in determining the punishment for the accused. As well as internal factors that come from the judge himself in considering a decision. Keywords: Children, Disparity, Considerations.